Active and passive vibration damping - Baz, Amr Mahmoud Sabry, 1945- (John Wiley & Sons, Inc., 2019)
A guide to the application of viscoelastic damping materials to control vibration and noise of structures, machinery, and vehicles Active and Passive Vibration Damping is a practical guide to the application of passive as well as actively treated viscoelastic damping materials to control vibration and noise of structures, machinery and vehicles. The author-a noted expert on the topic-presents the basic principles and reviews the potential applications of passive and active vibration damping technologies. The text presents a combination of the associated physical fundamentals, governing theories and the optimal design strategies of various configurations of vibration damping treatments. The text presents the basics of various damping effective treatments such as constrained layers, shunted piezoelectric treatments, electromagnetic and shape memory fibers. Classical and new models are included as well as aspects of viscoelastic materials models that are analyzed from the experimental characterization of the material coefficients as well as their modeling. The use of smart materials to augment the vibration damping of passive treatments is pursued in depth throughout the book. This vital guide: -Contains numerical examples that reinforce the understanding of the theories presented -Offers an authoritative text from an internationally recognized authority and pioneer on the subject -Presents, in one volume, comprehensive coverage of the topic that is not available elsewhere -Presents a mix of the associated physical fundamentals, governing theories and optimal design strategies of various configurations of vibration damping treatments Written for researchers in vibration damping and research, engineers in structural dynamics and practicing engineers, Active and Passive Vibration Damping offers a hands-on resource for applying passive as well as actively treated viscoelastic damping materials to control vibration and noise of structures, machinery and vehicles.